PRDX6 promotes proliferation and induces chemo-resistance via peroxidase activity in Toledo diffuse large B-cell lymphoma cells - Fang, Zhigang; Liu, Tingrong; Liu, Xiangfu; Lu, Ying; Sun, Yanling; Xiao, Ruozhi; Fan, Ruifang; Liu, Lingling (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphomas. Despite the application of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen being effective on 70–80% of DLBCL patients, the remaining 20–30% develop an even more aggressive relapsed tumor. PRDX6 has been shown to play important roles in multiple cancers. However, there is no study about the role of PRDX6 in DLBCL. Methods: The stable Toledo cell lines that overexpression or knockdown of PRDX6 gene were established. Western blot was used to determine the quantity of PRDX6 protein. Then, the function of PRDX6 in Toledo cell proliferation was determined using cell counting assay and Annexin V/PI analysis assays, and the underlying mechanism was determined through glutathione peroxidase activity and iPLA2 activity assay. Results: In the current study, we showed that the expression of PRDX6 was critical for the proliferation of Toledo DLBCL cells. Additionally, knockdown of PRDX6 induced apoptosis in Toledo DLBCL cells. Importantly, overexpression of PRDX6 caused a doxorubicin resistance in Toledo DLBCL cells, while downregulation of PRDX6 significantly enhanced doxorubicin induced apoptosis. Interestingly, the glutathione peroxidase activity of PRDX6, but not the phospholipase A2 activity, was crucial for PRDX6 induced proliferation and anti-apoptosis effects. Together, our study explored the tumor promoting function of PRDX6 in DLBCL for the first time. Conclusions: Our data indicated that PRDX6 could be a target for overcoming drug resistance. Targeting PRDX6 expression or peroxidase activity could be an effective strategy to overcome drug resistance in clinical DLBCL treatment.